Prenatal Diagnosis of a Case of Norrie Disease with Late Development of Bilateral Ocular Malformation. (4th May 2017) - Wu, Li Hong; Chen, Li-Hong; Xie, Hongning; Xie, Ying-Jun
ABSTRACT: We report a case of Norrie disease, diagnosed by prenatal ultrasound, confirmed by Sanger sequencing of the DNP gene from the aborted fetal cord blood and histologically. Prenatal ultrasound revealed no abnormality in either eye at 22 +1 and 31 +4 gestational weeks, but at 36 +5 gestational weeks both eyes had massive vitreous cavity opacities with complete retinal detachment. Norrie disease was initially suspected because of an older male sibling with the disease. To our knowledge, prenatal ultrasound diagnosis of Norrie disease has been previously described only one case in 1993 in a 34-week-old fetus. The normal eye development until after 31 + 4 gestational weeks provides insight into the first manifestation and then the rapid progression of the eye disease.